Surface-modified dielectric ceramic material, preparation method thereof, dielectric composite material and application of dielectric composite material

Through two calcining, titanate microsphere powder is prepared and specific organic groups are introduced, which solves the problems of insufficient dielectric performance and high loss of titanate powder materials at high frequencies, and achieves high dielectric constant and The effect of low dielectric loss.

CN119462129APending Publication Date: 2025-02-18SHANDONG SINOCERA FUNCTIONAL MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411608373.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing dielectric ceramic materials have problems of insufficient dielectric performance and high losses at high frequencies, especially titanate powder materials that are difficult to densify and surface treatment, which limits their use in high-frequency applications.

Method used

Titanate-based microsphere powder is prepared by two calcination and specific organic groups are introduced on its surface, which serves as a bridge to combine with inorganic powder and organic polymers to improve dielectric properties.

Benefits of technology

It improves the dielectric constant and reduces dielectric loss, enhances its compatibility and density with organic polymers, and is suitable for high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130276770000161
    Figure BDA0005130276770000161
  • Figure BDA0005130276770000171
    Figure BDA0005130276770000171
Patent Text Reader

Abstract

The invention discloses a surface-modified dielectric ceramic material, a preparation method thereof, a dielectric composite material and application of the dielectric composite.The surface-modified dielectric ceramic material comprises a base material, the base material is of a perovskite structure, and at least part of the surface of the base material is connected with organic groups. The organic group comprises at least one functional group of carboxylic acid, ester, acyl chloride, sulfonyl chloride, ketone, aldehyde, anhydride, amide and imide. According to the surface-modified dielectric ceramic material provided by the invention, the surface of the base material with a perovskite structure is modified, and a specific organic group is introduced into the surface of the base material. And a matrix material can be better compounded with an organic polymer, so that the dielectric property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric ceramic materials, and in particular to a surface-modified dielectric ceramic material, a preparation method thereof, a dielectric composite material and uses of the dielectric composite material. Background Art

[0002] In the 5G era, electronic devices are developing towards miniaturization, multifunctionality and lightweight, so materials with high dielectric constant and low dielectric loss have become a hot topic in the industry. To achieve the miniaturization and lightweight design of electronic devices, it is necessary to increase the dielectric constant of the material. At the same time, 5G high-frequency and high-speed transmission requires that the transmission loss of electronic devices is small. Therefore, in order to reduce the transmission loss, the dielectric loss tangent needs to be smaller. As an important component of electronic components, dielectric filling materials also need to have higher performance at high frequencies, including high dielectric constant and low dielectric loss. Ceramic fillers with high dielectric properties have very broad application prospects, such as capacitors, resonators, filters and signal receiving and transmitting antennas used in the communications industry and global positioning systems.

[0003] Ceramic materials have a higher dielectric constant, but high-temperature sintering is required when preparing ceramic powder materials. The resulting materials have disadvantages such as high porosity, poor mechanical properties, and high losses. Polymers have advantages such as good mechanical properties, excellent impact resistance, good electrical insulation, low dielectric loss, superior processing performance, light weight and low cost, but except for a few materials, their dielectric constants are usually low and dielectric losses are high. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a surface-modified dielectric ceramic material, a preparation method thereof, a dielectric composite material and an application of the dielectric composite material.

[0005] The present invention provides a surface-modified dielectric ceramic material, comprising a base material having a perovskite structure, and at least a portion of the surface of the base material is connected with an organic group, wherein the organic group comprises at least one functional group selected from the group consisting of carboxylic acid, ester, acyl chloride, sulfonyl chloride, ketone, aldehyde, anhydride, amide and imide.

[0006] The present invention also provides a method for preparing the above-mentioned surface-modified dielectric ceramic material, which comprises: preparing a base material by two calcinations, and then introducing organic groups on the surface of the base material.

[0007] The present invention also provides a dielectric composite material, comprising: resin and the above-mentioned surface-modified dielectric ceramic material.

[0008] The present invention also provides application of the dielectric composite material in the field of high dielectric constant copper clad laminates.

[0009] The present invention has the following beneficial effects:

[0010] The present invention provides a surface-modified dielectric ceramic material, a preparation method thereof, a dielectric composite material and an application of the dielectric composite material. The surface-modified dielectric ceramic material provided by the present invention introduces a specific organic group on the surface of a base material, and the specific organic group acts as a bridge to bond the base material and the organic polymer at the same time. After the base material with a perovskite structure is composited with a resin, the defects that are not conducive to the dielectric performance can be effectively reduced, and the dielectric performance can be further improved. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0012] Titanate ceramics with a special perovskite structure have a very high dielectric constant (εr~260) and a low dielectric loss (0.001~0.005), making them one of the most advantageous materials for preparing high dielectric and low loss materials. However, the sintering temperature of titanate powder materials is high, making it difficult to form by one-time sintering. In addition, since they need to be compounded with organic polymers when used as copper-clad laminate fillers, the titanate powder materials need to be surface treated to be more compatible with organic polymers and eliminate the defects therein. However, the current treatment of titanate powder materials is mostly carried out through doping modification. After high-temperature calcination, the number of surface groups decreases sharply, making the surface treatment of titanate powder materials difficult. Therefore, the surface treatment of titanate powder materials is rarely involved. This limits the application of titanate powder materials as high dielectric filling materials at high frequencies.

[0013] In view of the problems existing in the prior art, the present invention provides a dielectric ceramic material containing organic groups on the surface, a preparation method and an application thereof. The study found that after granulating the titanate powder material and calcining it twice, the prepared titanate microspheres have a density close to the theoretical density, not only have a high dielectric constant, but also have low dielectric loss. After that, they are treated with a surface treatment agent of a specific organic group to make them suitable for use as high dielectric filling materials at high frequencies. After being compounded with an organic polymer, the dielectric properties of the dielectric composite material are further improved. The overall preparation method is simple, the cycle is short, and the sintering temperature is ≤1400°C, which can meet the needs of industrial production.

[0014] The following specifically describes a surface-modified dielectric ceramic material, a preparation method thereof, a dielectric composite material, and applications of the dielectric composite material provided by an embodiment of the present invention.

[0015] In a first aspect, an embodiment of the present invention provides a surface-modified dielectric ceramic material, including a base material, the base material having a perovskite structure, and at least a portion of the surface of the base material is connected with an organic group, and the organic group includes at least one functional group of carboxylic acid, ester, acyl chloride, sulfonyl chloride, ketone, aldehyde, anhydride, amide, and imide.

[0016] In view of the problem that perovskite powder materials are difficult to surface treat, an embodiment of the present invention provides a surface-modified dielectric ceramic material, which can bond with both inorganic powders and organic matter by introducing specific organic groups on the surface of a base material with a perovskite structure, so that when it is used as a dielectric filling material, it can be better compatible with organic polymers, reduce the interface effect of the inorganic-organic composite system, thereby increasing the density of the dielectric composite material and achieving the purpose of improving the dielectric performance.

[0017] In some optional embodiments, the entire surface of the base material is connected with organic groups;

[0018] Preferably, the organic group is an organic group containing a long carbon chain, and the general formula of the organic group containing a long carbon chain is: x H 2x+3 O y A 4y )n, where x≥16, y≥4, n≥3, and A is any one of C, N, P, and S;

[0019] Preferably, the organic group containing a long carbon chain includes at least one of octyl pyrophosphate acyloxy, oleic acid acyloxy, isostearyl, stearic acid acyloxy, dodecylbenzenesulfonyl, dodecyltriethoxy, hexadecyltrimethoxy, hexadecyltriethoxy, and octadecyltrimethoxy.

[0020] In some optional embodiments, the matrix material has a perovskite structure;

[0021] Preferably, the composition of the matrix material is xCaTiO3-ySrTiO3-(1-xy)BaTiO3, 0≤x, y≤1;

[0022] Preferably, the particle size of the matrix material is 15-25 μm and the specific surface area is less than 0.2 m 2 / g, density is close to theoretical density, impurity content <0.1wt%;

[0023] Preferably, the dielectric composite material obtained by compounding the matrix material and the polytetrafluoroethylene resin in a mass ratio of 2:1 has a dielectric constant of 16.5-17.3 and a dielectric loss of 7×10 -4 -8×10 -4 .

[0024] In some optional embodiments, the contact angle of the surface-modified dielectric ceramic material is at most 160°.

[0025] In a second aspect, an embodiment of the present invention further provides a method for preparing the above-mentioned surface-modified dielectric ceramic material, which comprises: preparing a base material by two calcinations, and then introducing organic groups on the surface of the base material.

[0026] At present, when preparing dielectric ceramic materials, most of them are densified by multiple calcinations. This is because the sintering temperature of titanate powder materials is high and it is difficult to form by one sintering. However, after multiple calcinations, the number of groups on the surface of the powder is sharply reduced, which is not conducive to subsequent surface post-treatment. The present invention breaks through the convention and calcines the titanate powder materials twice at a lower temperature after granulation. Not only can the high densification of the titanate powder materials be achieved, but also the prepared titanate microsphere powder has a higher dielectric constant and lower dielectric loss, and is easy to surface modify or modify. After being treated with a surface treatment agent containing a specific organic group, the organic group acts as a bridge, which can not only bond with the surface group of the titanate powder material, but also can be compounded with an organic polymer such as PTFE. The prepared dielectric composite material of titanate powder material / PTFE can effectively reduce the defects that are not conducive to dielectric properties and further improve the dielectric properties.

[0027] In some optional embodiments, the preparation of the matrix material comprises the following steps: wet-grinding the raw material mixture, drying and pre-sintering to obtain a pre-sintered material; wet-grinding the pre-sintered material, granulating, debinding and sintering once to obtain a first green body; wet-grinding the first green body, granulating, debinding and sintering twice to obtain a second green body; sieving the second green body to obtain a matrix material powder;

[0028] Preferably, the wet sand milling comprises: mixing the powder with yttrium-stabilized zirconia balls and deionized water for sand milling, controlling the solid content to be 18-22%, sand milling 3-5 times, and obtaining a uniform mixed material;

[0029] Preferably, the binder used for granulation is a polyvinyl alcohol solution with a mass concentration of 3-5%;

[0030] Preferably, the pre-burning conditions are: keeping at 1000±5°C for 3-4h under normal pressure;

[0031] Preferably, the conditions for the first sintering are: sintering at 1380±5°C for 3-4h under normal pressure, and the conditions for the second sintering are: sintering at 1400±5°C for 3-4h under normal pressure; ensuring that the powder is calcined densely and still maintains the sphericity of the powder, and the particles do not stick together.

[0032] Preferably, the temperature of the debinding treatment is 650±5° C. and the time is 3-4 hours to completely remove organic impurities.

[0033] In some optional embodiments, introducing organic groups on the surface of the base material comprises the following steps: dry-milling the base material powder, mixing it with a surface modifier and milling it for a period of time to obtain a surface-modified dielectric ceramic material;

[0034] Preferably, the method comprises the following steps: ball milling and mixing the matrix material powder and the yttrium-stabilized zirconia balls at a mass ratio of 1:3-1:4 at a rotation speed of 300-400 rpm, adding a surface modifier during the mixing process, ball milling for 20-45 minutes, and drying at 120±5° C. for 12-15 hours to obtain a surface-modified dielectric ceramic material;

[0035] Preferably, the amount of the surface treatment agent used is 0.2-1 wt % of the total mass of the base material powder.

[0036] The embodiment of the present invention provides a method for preparing the above-mentioned surface-modified dielectric ceramic material, which uses titanate powder material as the main component, provides high dielectric constant and low dielectric loss. In view of the problem that titanate powder is difficult to densify, the solution provided by the present invention is to calcine the titanate powder material twice at a relatively low temperature to ensure that the microspheres after granulation are calcined and dense. The test results show that the dielectric properties of the titanate powder material after the two calcinations are significantly enhanced, and the density of the microspheres is significantly improved, and the specific surface area is less than 0.2m 2 / g, using it as a matrix material is beneficial to enhancing the dielectric properties, and the presence of surface groups such as hydroxyl groups is beneficial to subsequent surface treatment. After that, a surface treatment agent with a specific organic group is used for surface treatment to introduce specific organic groups on the surface of the titanate powder material. The surface treatment agent can not only bond with the surface groups of the titanate powder material, but also be compounded with organic polymers such as polytetrafluoroethylene resin. The surface of the modified titanate powder material changes from hydrophilic to super-hydrophobic, and the contact angle can reach about 160°. It can be better compounded with organic polymers such as resins such as PTFE, and through density testing, it can reach more than 98% of the theoretical density. Thereby further improving some dielectric constants and significantly reducing dielectric losses.

[0037] Furthermore, in the solution provided by the present invention, in the process of surface modification of titanate powder materials, the relationship between performance and the content of the surface treatment agent is fully considered, and the amount of the surface treatment agent is controlled to be 0.2-1wt% of the total mass of the titanate powder material. An amount below 0.2wt% will result in the inorganic groups on the powder surface not being completely occupied by the organic surface treatment agent, thereby poor compatibility with the organic resin, and the introduction of defects such as voids during the composite process, resulting in reduced dielectric properties; an amount above 1wt% will cause the surface treatment agent containing organic groups with long carbon chains to self-entangle and fail to be evenly distributed with the titanate powder material, which will also result in reduced dielectric properties.

[0038] In a third aspect, an embodiment of the present invention further provides a dielectric composite material, comprising: a resin and the above-mentioned surface-modified dielectric ceramic material. For example, the present invention provides a high-frequency PCB board substrate, comprising PTFE resin and the above-mentioned surface-modified dielectric ceramic material.

[0039] In some optional embodiments, the density of the dielectric composite material is above 98% of the theoretical density;

[0040] Preferably, the resin is a thermoplastic resin, preferably a polytetrafluoroethylene resin;

[0041] Preferably, the dielectric composite material obtained by compounding the surface-modified dielectric ceramic material with the polytetrafluoroethylene resin in a mass ratio of 2:1 has a dielectric constant of ≥18.8 and a dielectric loss of ≤4×10 -4 .

[0042] The embodiment of the present invention also provides a dielectric composite material, comprising: a resin and the above-mentioned surface-modified dielectric ceramic material, a specific organic group is introduced on the surface of a titanate powder material, the introduced organic group has a polarity similar to that of a polytetrafluoroethylene resin, and according to the principle of like dissolves like, the internal defects of the titanate powder material and the polytetrafluoroethylene resin can be reduced and the dielectric properties can be improved after the composite material is composited. At the same time, since the organic group containing a long carbon chain is more tightly entangled in the composite with a resin such as a polytetrafluoroethylene resin, it is less likely to fall off during the mixing process, ensuring that the titanate powder material and the polytetrafluoroethylene resin are mixed evenly, the purpose of improving the performance can also be achieved.

[0043] In a fourth aspect, embodiments of the present invention further provide applications of the above-mentioned dielectric composite material in the field of high dielectric constant copper clad laminates.

[0044] The present invention will be further described below in conjunction with the embodiments.

[0045] Example 1

[0046] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination, and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The specific surface area of ​​the strontium titanate powder is 0.12m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0047] Example 2

[0048] After the calcium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase calcium titanate. After sand-milling and mixing again, they are granulated with glue to obtain pre-sintered materials. The pre-sintered materials are kept at 1380°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination and sieved to obtain the matrix material. The calcium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.15m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, calcium titanate ceramic powder treated with specific surface groups is obtained.

[0049] Example 3

[0050] After the barium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase barium titanate. After sand-milling and mixing again, they are granulated with glue to obtain pre-sintered materials. The pre-sintered materials are kept at 1380°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination and sieved to obtain the matrix material. The barium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.09m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, barium titanate ceramic powder treated with specific surface groups is obtained.

[0051] Example 4

[0052] Calcium carbonate, strontium carbonate, barium carbonate and titanium oxide powders are sand-milled and mixed evenly, and then pre-sintered and kept at 1005°C for 3 hours to synthesize a powder composition. Then, sand-milled and mixed evenly again, glue is added and granulated to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain a first green body. The first green body is sand-milled and mixed evenly again, and then glue is added and granulated. The powder is kept at 1405°C for 3 hours for a second calcination, and sieved to obtain a matrix material. The 0.2CaTiO3-0.5SrTiO3-0.3BaTiO3 composite powder with a particle size of 15μm after two calcinations is mixed with a 5mm zirconium ball in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.13m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, a powder composite filler treated with specific surface groups is obtained.

[0053] Example 5

[0054] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1375°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1395°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.12m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0055] Example 6

[0056] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.10m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 1wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0057] Example 7

[0058] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 21μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.10m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl di(methacryloyl) isostearyl titanate is added to the powder mass, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0059] Example 8

[0060] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 24μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.10m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl tri(dodecylbenzenesulfonyl) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0061] Example 9

[0062] After the calcium carbonate, strontium carbonate, barium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-fired first and kept at 1000°C for 3 hours to synthesize a powder composition. After sand-milling and mixing again, they are granulated with glue to obtain a pre-fired material. The pre-fired material is kept at 1385°C for 3 hours for a first calcination to obtain a first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination and sieved to obtain a matrix material. The 0.5CaTiO3-0.2SrTiO3-0.3BaTiO3 composite powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.13m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, a powder composite filler treated with specific surface groups is obtained.

[0063] Example 10

[0064] Calcium carbonate, strontium carbonate, barium carbonate and titanium oxide powders are sand-milled and mixed evenly, and then pre-sintered and kept at 1000°C for 3 hours to synthesize a powder composition. Then, they are sand-milled and mixed evenly again, and then granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1385°C for 3 hours for a first calcination to obtain a first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination, and sieved to obtain a matrix material. The 0.2CaTiO3-0.3SrTiO3-0.5BaTiO3 composite powder with a particle size of 15μm after two calcinations is mixed with a 5mm zirconium ball in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.13m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, a powder composite filler treated with specific surface groups is obtained.

[0065] Comparative Example 1

[0066] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1400°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.10m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. After ball milling for 0.5h and drying in an oven at 120℃ for 12h, the strontium titanate ceramic powder without surface treatment is obtained.

[0067] Comparative Example 2

[0068] After the calcium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase calcium titanate. After sand-milling and mixing again, they are granulated with glue to obtain pre-sintered materials. The pre-sintered materials are kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination and sieved to obtain the matrix material. The calcium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene tank for ball milling. The powder has a specific surface area of ​​0.15m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. After ball milling for 0.5h and drying in an oven at 120℃ for 12h, the calcium titanate ceramic powder without surface treatment is obtained.

[0069] Comparative Example 3

[0070] After the barium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 995°C for 3 hours to synthesize pure phase barium titanate. After sand-milling and mixing again, they are granulated with glue to obtain pre-sintered materials. The pre-sintered materials are kept at 1385°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination and sieved to obtain the matrix material. The barium titanate powder with a particle size of 15μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.09m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. After ball milling for 0.5h and drying in an oven at 120℃ for 12h, the barium titanate ceramic powder without surface treatment is obtained.

[0071] Comparative Example 4

[0072] Calcium carbonate, strontium carbonate, barium carbonate and titanium oxide powders are sand-milled and mixed evenly, and then pre-sintered and kept at 1000°C for 3 hours to synthesize a powder composition. Then, they are sand-milled and mixed evenly again, and then granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain a first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination, and sieved to obtain a matrix material. The 0.2CaTiO3-0.5SrTiO3-0.3BaTiO3 composite powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.13m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. After ball milling for 0.5h, it is dried in an oven at 120℃ for 12h to obtain a powder composite filler without surface treatment.

[0073] Comparative Example 5

[0074] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1350°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.25m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0075] Comparative Example 6

[0076] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain the first green body. After the first green body is sand-milled and mixed evenly again, they are granulated with glue. The powder is kept at 1450°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 10μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.20m2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0077] Comparative Example 7

[0078] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. Then, after sand-milling and mixing evenly again, they are granulated with glue to obtain pre-sintered materials. The pre-sintered materials are kept at 1380°C for 3 hours for calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 30μm after the first calcination is mixed with 5mm zirconium balls in a polytetrafluoroethylene tank for ball milling. The powder has a specific surface area of ​​0.48m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 0.5wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0079] Comparative Example 8

[0080] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1395°C for 3 hours for a second calcination, and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.12m 2 / g, the mass ratio of powder to zirconium ball is 1:3, the rotation speed is 300rpm. During the mixing process, 0.5wt% of γ-methacryloxypropyltrimethoxysilane is added to the powder mass, and after ball milling for 0.5h, the surface-treated strontium titanate ceramic powder is obtained after drying in an oven at 120°C for 12h.

[0081] Comparative Example 9

[0082] After the strontium carbonate and titanium oxide powders are sand-milled and mixed evenly, they are pre-sintered first and kept at 1000°C for 3 hours to synthesize pure phase strontium titanate. After sand-milling and mixing again, they are granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain the first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1395°C for 3 hours for a second calcination and sieved to obtain the matrix material. The strontium titanate powder with a particle size of 18μm after two calcinations is mixed with 5mm zirconium balls in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.10m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 1.5wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, strontium titanate ceramic powder treated with specific surface groups is obtained.

[0083] Comparative Example 10

[0084] Calcium carbonate, strontium carbonate, barium carbonate and titanium oxide powders are sand-milled and mixed evenly, and then pre-sintered and kept at 1005°C for 3 hours to synthesize a powder composition. Then, they are sand-milled and mixed evenly again, and then granulated with glue to obtain a pre-sintered material. The pre-sintered material is kept at 1380°C for 3 hours for a first calcination to obtain a first green body. The first green body is sand-milled and mixed evenly again, and then granulated with glue. The powder is kept at 1405°C for 3 hours for a second calcination, and sieved to obtain a matrix material. The 0.5CaTiO3-0.2SrTiO3-0.3BaTiO3 composite powder with a particle size of 15μm after two calcinations is mixed with a 5mm zirconium ball in a polytetrafluoroethylene jar for ball milling. The powder has a specific surface area of ​​0.13m 2 / g, the mass ratio of powder to zirconium ball is 1:3, and the rotation speed is 300rpm. During the mixing process, 2wt% of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate is added, and after ball milling for 0.5h and drying in an oven at 120°C for 12h, a powder composite filler treated with specific surface groups is obtained.

[0085] Performance Testing:

[0086] The ceramic powders obtained in Examples 1 to 10 and Comparative Examples 1 to 10 were subjected to the following performance tests:

[0087] (1) Dielectric properties: The ceramic powder and PTFE were weighed in a mass ratio of 2:1, mixed evenly and pressed into tablets. After sintering, the dielectric properties were tested using the TE01δ method at a test frequency of 6.4 GHz.

[0088] (2) Density: The density of the columnar sample after the ceramic powder and PTFE are compounded is tested using an Archimedes buoyancy density meter and the ratio is compared with the theoretical density.

[0089] The test results of the above embodiments and comparative examples are shown in Table 1.

[0090] Table 1

[0091]

[0092]

[0093] It can be seen from the above table that the particle size of the dielectric ceramic powder after two-step calcination is less than 15μm or greater than 25μm. Although the performance is improved after modification with a specific organic group content of 0.2wt%-1wt%, the particle size affects the number of surface groups, so the content of the organic group required for modification is different, which affects the composite with PTFE resin. Therefore, the performance cannot meet the use requirements of high dielectric constant and low dielectric loss. At the same time, too little or too much content of specific organic groups on the surface of dielectric ceramic powder will affect the composite with resin. Only dielectric ceramic powder modified with a specific organic group content of 0.2-1wt% has a dielectric constant ≥18.8 and a dielectric loss ≤4×10 -4 The dielectric properties can meet the use requirements in the field of high dielectric constant copper clad laminates.

[0094] Application Example 1

[0095] The surface treated strontium titanate ceramic powder of Example 1 was mixed with PTFE emulsion and curing agent, and then rolled and sintered to form a copper clad laminate. The dielectric properties of the laminate were tested by the strip line method. The dielectric constant was 18.5 and the dielectric loss was 2.1×10 -3 , to meet the use requirements of high-frequency copper clad laminates.

[0096] Application Example 2

[0097] The calcium titanate ceramic powder after surface treatment in Example 2 was mixed with PTFE emulsion and curing agent, and then rolled and sintered to form a copper-clad laminate. The stripline method was used to test the dielectric properties of the laminate. The dielectric constant was 18.2 and the dielectric loss was 1.9×10 -3 , to meet the use requirements of high-frequency copper clad laminates.

[0098] Application Example 3

[0099] The 0.2CaTiO3-0.5SrTiO3-0.3BaTiO3 powder composition after surface treatment in Example 4 was mixed with PTFE emulsion and curing agent, and then rolled and sintered, and then hot-pressed and copper-clad to obtain a copper-clad laminate. The dielectric properties of the laminate were tested by the stripline method, and the dielectric constant was 18.6 and the dielectric loss was 2.2×10 -3 , to meet the use requirements of high-frequency copper clad laminates.

[0100] Application Comparative Example 1:

[0101] The strontium titanate ceramic powder composition without surface treatment in Comparative Example 1 was mixed with PTFE emulsion and curing agent, and then rolled and sintered to form a copper-clad laminate. The dielectric properties of the laminate were tested by the stripline method. The dielectric constant was 14.5 and the dielectric loss was 5.5×10 -3 , does not meet the use requirements of high-frequency copper clad laminates.

[0102] Application Comparative Example 2:

[0103] The 0.2CaTiO3-0.5SrTiO3-0.3BaTiO3 ceramic powder composition without surface treatment in Comparative Example 4 was mixed with PTFE emulsion and curing agent, and then rolled and sintered, and then hot-pressed and copper-clad to obtain a copper-clad laminate. The dielectric properties of the laminate were tested by the stripline method, and the dielectric constant was 14.7 and the dielectric loss was 5.3×10 -3 , does not meet the use requirements of high-frequency copper clad laminates.

[0104] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A surface-modified dielectric ceramic material, characterized in that: It includes a base material, the base material has a perovskite structure, and at least part of the surface of the base material is connected with an organic group, and the organic group includes at least one functional group of carboxylic acid, ester, acyl chloride, sulfonyl chloride, ketone, aldehyde, anhydride, amide, and imide.

2. The surface-modified dielectric ceramic material according to claim 1, characterized in that: The entire surface of the base material is connected with organic groups; Preferably, the organic group is an organic group containing a long carbon chain, and the general formula of the organic group containing a long carbon chain is: (C x H 2x+3 O y A 4y )n, where x≥16, y≥4, n≥3, and A is any one of C, N, P, and S; More preferably, the organic group containing a long carbon chain includes at least one of octyl pyrophosphate acyloxy, oleic acid acyloxy, isostearyl, stearic acid acyloxy, dodecylbenzenesulfonyl, dodecyltriethoxy, hexadecyltrimethoxy, hexadecyltriethoxy, and octadecyltrimethoxy.

3. The surface-modified dielectric ceramic material according to claim 1, characterized in that: The matrix material has a perovskite structure; Preferably, the composition of the matrix material is xCaTiO3-ySrTiO3-(1-xy)BaTiO3, 0≤x, y≤1; Preferably, the particle size of the matrix material is 15-25 μm, and the specific surface area is less than 0.2 m 2 / g, density is close to theoretical density, impurity content <0.1wt%; Preferably, the dielectric composite material obtained by compounding the matrix material and the polytetrafluoroethylene resin in a mass ratio of 2:1 has a dielectric constant of 16.5-17.3 and a dielectric loss of 7×10 -4 -8×10 -4 .

4. The surface-modified dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The contact angle of the surface-modified dielectric ceramic material is at most 160°.

5. A method for preparing a surface-modified dielectric ceramic material according to any one of claims 1 to 4, characterized in that: It includes: The matrix material is prepared by calcining twice, and then organic groups are introduced on the surface of the matrix material.

6. The preparation method according to claim 5, characterized in that: The preparation of the matrix material comprises the following steps: wet-grinding the raw material mixture, drying and pre-sintering to obtain a pre-sintered material; wet-grinding the pre-sintered material, granulating, debinding and sintering to obtain a first green body; wet-grinding the first green body, granulating, debinding and sintering to obtain a second green body; sieving the second green body to obtain a matrix material powder; Preferably, the wet sand milling comprises: mixing the powder with yttrium-stabilized zirconia balls and deionized water for sand milling, controlling the solid content to be 18-22%, sand milling 3-5 times, and obtaining a uniform mixed material; Preferably, the binder used for granulation is a polyvinyl alcohol solution with a mass concentration of 3-5%; Preferably, the pre-burning conditions are: keeping warm at 1000±5°C for 3-4h under normal pressure; Preferably, the conditions for the primary sintering are: sintering at 1380±5°C for 3-4h under normal pressure, and the conditions for the secondary sintering are: sintering at 1400±5°C for 3-4h under normal pressure; Preferably, the debinding treatment is carried out at a temperature of 650±5° C. for 3-4 hours.

7. The preparation method according to claim 6, characterized in that: Introducing organic groups on the surface of the base material comprises the following steps: dry-milling the base material powder, mixing it with a surface modifier and milling it for a period of time to obtain a surface-modified dielectric ceramic material; Preferably, the method comprises the following steps: ball milling and mixing the matrix material powder and the yttrium-stabilized zirconia balls at a mass ratio of 1:3-1:4 at a rotation speed of 300-400 rpm, adding a surface modifier during the mixing process, ball milling for 20-45 minutes, and drying at 120±5° C. for 12-15 hours to obtain a surface-modified dielectric ceramic material; Preferably, the amount of the surface treatment agent is 0.2-1 wt % of the total mass of the base material powder.

8. A dielectric composite material, characterized in that: The invention comprises: a resin and the surface-modified dielectric ceramic material according to any one of claims 1 to 4.

9. The dielectric composite material according to claim 8, characterized in that: The resin is a thermoplastic resin, and the resin is preferably a polytetrafluoroethylene resin; Preferably, the density of the dielectric composite material is above 98% of the theoretical density; Preferably, the dielectric composite material obtained by compounding the surface-modified dielectric ceramic material with polytetrafluoroethylene resin in a mass ratio of 2:1 has a dielectric constant of ≥18.8 and a dielectric loss of ≤4×10 -4 .

10. Use of the dielectric composite material according to claim 8 or 9 in the field of high dielectric constant copper clad laminates.